The Emperor is back! Rediscovery and redescription of the holotype of Pandinus imperator (Scorpiones: Scorpionidae) - Holstein, Joachim; Wendt, Ingo; Rossi, Andrea (Arachnologische Mitteilungen, 2017)

(untitled)
The holotype of the Emperor Scorpion Pandinus imperator (C.L. Koch, 1841) was long believed to have been lost. In 2015, as scientists at the State Museum of Natural History in Stuttgart were digitizing its entomological collections, they rediscovered the specimen on which Koch had based his description of the scorpion in 1841.